1987
DOI: 10.1007/bf02776721
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of glucagon and insulin in therapy of fulminant hepatitis

Abstract: Forty five patients were examined in order to evaluate the usefulness of glucagon and insulin as a therapy of fulminant hepatitis. Thirty patients were treated with simultaneous infusion of glucagon and insulin, whereas prednisolone was given at a daily dose of 60 to 90 mg in 15 cases. In the former group, 1 mg of glucagon and 10 units of regular insulin were infused over a period of 2 to 6 hours. Two such treatments were given per day in the early critical period of fulminant hepatitis. The therapeutic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Baker et al (4) found that GI infusion tended to improve the mortality rate in patients with alcoholic hepatitis. Okita et al ( 5 ) reported that the survival rate was higher in patients with fulminant hepatitis treated with GI, and Oka et al (6) suggested that GI treatment for severe hepatitis may stimulate recovery of the liver. Thus GI seems to be somewhat effective, but the clinical effects of GI therapy on liver regeneration and survival rate of such patients are still not satisfactory.…”
mentioning
confidence: 99%
“…Baker et al (4) found that GI infusion tended to improve the mortality rate in patients with alcoholic hepatitis. Okita et al ( 5 ) reported that the survival rate was higher in patients with fulminant hepatitis treated with GI, and Oka et al (6) suggested that GI treatment for severe hepatitis may stimulate recovery of the liver. Thus GI seems to be somewhat effective, but the clinical effects of GI therapy on liver regeneration and survival rate of such patients are still not satisfactory.…”
mentioning
confidence: 99%